Influence of personality and military membership on relationship satisfaction - Shoemaker, Cassandra R. (University of Wisconsin--Stout. Office of Research and Sponsored Programs, 2017)
Purpose: Previous research has shown that men in the military have less relationship satisfaction then civilian men, regardless of being married or not (McLeland & Sutton, 2005). Other research has shown that military training does change service members’ personality (Thoemmes, Jonkmann, Lüdtke, & Trautwein, 2012). The purpose of this study was to see how United States military service members’ relationship satisfaction changes between the time before they enter into service and during their time in service, as well as to examine the relationship between personality and relationship satisfaction in the military population. Method: Sixty-nine participants took an online survey through Qualtrics that assessed their personalities and relationship satisfaction using the OCEAN.20 Inventory and ENRICH Assessment. Results: Results showed no significant correlations between personality characteristics and relationship satisfaction or between the two different time points.
Research article with tables.
Keywords: relationship satisfaction; military; Personality; Veterans; Soldiers--Family relationships; United States. Army--Military life; Soldiers--Psychology